Kelayakan Usahatani Jagung Hibrida di Kabupaten Kendal (Studi Kasus di Desa Sidodadi Kecamatan Patean Kab. Kendal) - Anggi Sahru Romdon; Johanes Amirrullah (Seminar Nasional Lahan Suboptimal, 2019)
Romdon AS, Amirullah J 2019. The feasibility of hybrid corn farming in Kendal District (Case Study in Sidodadi Village Patean Sub-district Kendal District). in: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 345-352. Palembang: Unsri Press. Kendal District is the fourth contributor to corn production in Central Java after Grobogan, Blora and Wonogiri district. Kendal district corn production in 2017 reached 239,690 tons with an average productivity of 68.03 ku/ha. Productivity is still relatively low compared to the achievement of productivity in other districts in Central Java such as Cilacap (72.54 ku/ha), Sukoharjo (87.52 ku/ha), Klaten (81.60 ku/ha), and Batang (78.84 ku/ha), as well as Results showed that achievable productivity ranged from 85-110 ku/ha. The purpose of research is to know the general overview of the region, the general picture of corn farming and the feasibility of corn farming done by farmers in Kendal district. English translation. The focus of research was conducted in Sidodadi village of Patean Sub-district, since 31.7% of the area of the Patean corn sub-harvest is located in the village. Varieties of corn that is common in the planting are pioneer and Bisi, OPT control is done by Prefentive and when there is attack while fertilization is done by the average dose used is Urea 350-475 kg/ha and Phonska 300 kg/ha. Corn farming done by farmers in general 2 times in 1 year in the planting season II (MK 1) and planting season III (MK 2), the results of farming analysis shows that corn farming is worth the effort to be seen from NPV 35.40 and IRR 404%.Keywords:  corn, farming, Kendal, NPV, productivity